Better non-invasive endoscopic procedure: endoscopic ultrasound or magnetic resonance cholangiopancreatography? - Azra Rašić; Amela Sofić; Semir Bešlija; Ismar Rašić; Berisa Hasanbegović (Medicinski glasnik, 2018)
Aim: To compare the effect of neoadjuvant chemotherapy based on taxane and/or anthracycline to the extent of an objective response in female patients with unresectable breast cancer with evaluation of the toxic profile of applied chemotherapy. Methods: One hundred patients with histologically verified breast cancer, treated with neoadjuvant chemotherapy were divided into two groups: a study group A (50 patients), who had received 4 to 6 cycles of taxane-based chemotherapy, and control group B (50 patients), who had received 4 to 6 cycles of anthracyclines-based chemotherapy. Pathohistological response was evaluated after tumour excision and axillary resection at the end of chemotherapy and it was defined as pathologic complete (pCR), partial (pPR), or no response (pNR). Toxic effects were evaluated and quantified by the Common Terminology Criteria for Adverse Events v4.0. Results: After neoadjuvant chemotherapy, 8% of patients in the group A achieved pCR, 54% achieved pPR, while 38% of patients had no tumour response to applied chemotherapy. In the group B pCR was achieved in 6%, pPR in 42% of patients, while 51% of patients were pNR to the administered chemotherapy. Significant reduction of tumour mass was achieved in the group of patients treated with taxanes: 20.00 (7.75-30.25) vs. 13.50 (6.00-25.00) mm (p=0.024). Toxicity of chemotherapy in group A and group B was within the limits of grade 2. Conclusion: The addition of taxane to anthracycline-based neoadjuvant chemotherapy in patients with breast cancer resulted in a significant reduction in tumour mass compared to the group of patients treated with anthracyclines, but without increasing the overall side effects.
Keywords: tumour reduction; anthracyclines; taxanes